Determination of elastic modulus of claystone: Nano-/micro-indentation and meso-compression tests used to investigate impact of alkaline fluid propagation over 18 years - Danièle Bartier; Christophe Auvray (Journal of Rock Mechanics and Geotechnical Engineering, 2017)
Micro-mechanical properties of a claystone were tested after undergoing alkaline perturbation on site (Tournemire, CD borehole) for 18 years. In a saturated context and outside the excavation disturbed zone (EDZ), the claystone exhibits a 11.6-mm black rim at the cement/paste interface, which shows a different mechanical behaviour from the rest of the claystone. Three sets of measurements of elastic modulus were performed using: (i) nano-indentation tests with a constant indentation depth of 2 μm, (ii) micro-indentation tests with a constant indentation depth of 20 μm, and (iii) meso-compression tests with a constant displacement of 200 μm. The increase of the modulus of deformability in the black rim is between 15 GPa and 20 GPa according to the scale. Moreover, an overall decrease of the modulus of deformability from the smallest to the largest scale is observed in each zone. In view of the mineralogy and petrographic observations, higher values of modulus of deformability in the black rim are related to carbonate content and its distribution. Precipitation of cementitious carbonates as inclusions and very thin partings leads to hardening of the claystone.